Effect of steel fiber shape and content on printability, microstructure and mechanical properties of 3D printable high strength cementitious materials - Zijian Jia; Mengting Zhou; Yu Chen; Wei Wang; Lei Ma; Yuning Chen; Chao Liu; Yamei Zhang (Case Studies in Construction Materials, 2024)
This study investigates the effects of steel fiber shape (straight and hooked-end) and content (0, 0.5, 1.0, and 1.5 vol%) on rheological properties, printability, mechanical performance and microstructure of 3D printable steel fiber reinforced high strength concrete (3DP-SFHSC). The results indicate that the increase of fiber content improves the mechanical behaviors of 3DP-SFHSC, but the extrudability suffers from reduction when the fiber content exceeded 1.0 vol% due to the significant increase in yield stress. The addition of 1.5 vol% hooked-end fibers enhances the compressive strength of 3DP-SFHSC by 8%, 25.7%, and 40.4% in the X, Y, and Z directions, respectively. Additionally, it also improves the tensile strength in the X direction by 37.67%. The printed specimens exhibit weaker mechanical properties compared to the cast specimens. On the one hand, the lower fiber-matrix compactness resulting from the absence of vibration during printing leads to increased porosity and weak bonding between the steel fibers and matrix. On the other hand, the inconsistent movement between fibers and mortar matrix during extrusion process may also cause the formation of gaps around fibers. Straight fibers show pronounced enhancements in buildability, compressive strength and tensile strength compared to hooked-end fibers at the same fiber volume fraction. Straight fibers align easily during the extrusion process, contributing to a matrix with lower porosity and smaller average pore size.